Revisiting Italian borrowings in the OED - Pinnavaia, L (2010)
In honor of the tenth anniversary of the online version of the OED, I would like to return to the question of the Italian borrowings in the OED. At the time of the publication of "The Italian borrowings in the Oxford English Dictionary" (2001), based upon the second edition of the dictionary, the lexicographers at OUP had already started revising the entries regarding these loans from the Italian language. In these last ten years, their draft revisions have not only eliminated some earlier etymological uncertainties, updated first and last attestations, but also remove and added words from the English word-stock deriving from Italian. In this paper, I would thus like to observe more closely the differences between the state of the Italianisms in the second and third editions of the OED. The point of this paper will essentially be two-fold. One the one hand, it will attempt to measure the extent of the lexicographers' work in these last ten years; on the other, it will try to understand the areas of influence Italian has had upon English in the last decade. This will be carried out by comparing and contrasting the data held in Pinnavaia (2001) with the Italianisms collected in the OED online. The main areas of investigation will principally concern the lexemes included, their etymologies, and their examples of use.